A Case Study of Mosaic Trisomy 13 in a 2-year-old Filipino Child - Padilla, Carmencita D (Archīum Ateneo, 2020)
Mosaic trisomy 13 is estimated to occur in 5% of all trisomy 13 cases. Presentation of trisomy 13 mosaicism is highly variable, with cases that may present with a normal phenotype and intellectual function, to cases with grossly abnormal features and profound developmental delays. We present a 2-year-old female with trisomy 13 mosaicism, who presented with small for gestational age (SGA), polydactyly, ventricular septal defect (VSD), and poor oral feeding.